Total Flavonoids of Rhizoma Drynariae Enhances Angiogenic-Osteogenic Coupling During Distraction Osteogenesis by Promoting Type H Vessel Formation Through PDGF-BB/PDGFR-β Instead of HIF-1α/ VEGF Axis - Shen, Zhen; Chen, Zehua; Li, Zige; Zhang, Yan; Jiang, Tao; Lin, Haixiong; Huang, Minling; Chen, Huamei; Feng, Junjie; Jiang, Ziwei (Frontiers in Pharmacology, 2020)
Background: Total flavonoids of Rhizoma Drynariae (TFRD), extracted from the kidney-tonifying traditional Chinese medicine Rhizoma Rrynariae, has been proved to be effective in treating osteoporosis, bone fractures and defects. However, pharmacological effects of TFRD on type H vessels, angiogenic-osteogenic coupling in distraction osteogenesis (DO) and the mechanism remain unclear. This study aims at investigating whether type H vessels exist in the DO model, effects of TFRD on angiogenic-osteogenic coupling and further elucidating the underlying mechanism. Methods: Rats models of DO and bone fracture (FR) were established, and then were separately divided into TFRD and control subgroups. Imageological and histological analyses were performed to assess bone and vessel formation. Double immunofluorescent staining for CD31 and endomucin was conducted to determine type H vessel formation. Matrigel tube formation, ALP and Alizarin Red S staining assays were performed to test the effects of TFRD on angiogenesis or osteogenesis of endothelial precursor cells (EPCs) or bone marrow-derived mesenchymal stem cells (BMSCs). Additionally, expression levels of HIF-1α, VEGF, PDGF-BB, RUNX2 and OSX were determined by ELISA, qPCR or western blot, respectively. Results: The in vivo results indicated more formed type H vessels in DO groups than in FR groups and TFRD obviously increased the abundance of type H vessels. Moreover, groups with higher abundance of type H vessels showed better angiogenesis and osteogenesis outcomes. Further in vitro experiments showed that TFRD significantly promoted while blocking PDGF-BB remarkably suppressed the angiogenic activity of EPCs under strained conditions. The levels of p-AKT and p-ERK1/2, downstream mediators of the PDGF-BB pathway, were up-regulated by TFRD but blocked by function blocking anti-PDGF-BB antibody. In contrast, the activated AKT and ERK1/2 and corresponding tube formation were not affected by the HIF-1α inhibitor. Besides, blocking PDGF-BB inhibited the osteogenic differentiation of the strained BMSCs, but TFRD enhanced osteogenic activity of BMSCs and ameliorated the inhibition, with more calcium nodes, higher ALP activity and mRNA and protein levels of RUNX2 and OSX. Conclusions: Type H vessels exist in the DO model and TFRD enhances angiogenic- osteogenic coupling during DO process by promoting type H vessel formation via PDGF-BB/PDGFR-β instead of HIF-1α/VEGF axis.